Under the Greenwood Tree; Or, The Mellstock Quire : A Rural Painting of the Dutch School - Hardy, Thomas, 1840-1928 (Salt Lake City, UT : Project Gutenberg, 2001)
"Under the Greenwood Tree; Or, The Mellstock Quire" by Thomas Hardy is a novel published in 1872. Set in the fictional village of Mellstock, it follows young Dick Dewy, a member of the traditional parish choir, as he falls for the beautiful new schoolmistress, Fancy Day. When a new vicar threatens to replace the choir's string music with a modern organ, Dick must navigate both the changing times and romantic rivalry from wealthier suitors competing for Fancy's affections in this charming portrait of rural English life. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Under_the_Greenwood_Tree
Release date is 2001-06-01
David Price, Margaret Rose Price and Dagny
Keywords: Musical fiction; Love stories; Courtship -- Fiction; Pastoral fiction; Wessex (England) -- Fiction; Church musicians -- Fiction; Choirs (Music) -- Fiction; Women teachers -- Fiction